ANALISIS HUBUNGAN CORPORATE SOCIAL RESPONSIBILITY DAN CORPORATE FINANCIAL PERFORMANCE PADA PERBANKAN SYARIAH DI INDONESIA - Nibras Anny Khabibah; Siti Mutmainah (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to determine the relationship between Corporate Social Responsibility (CSR) and Corporate Financial Performance (CFP) on Islamic Banking in Indonesia in 2003-2011. CSR variable is examined using Islamic Social Reporting (ISR) Index, whereas CFP variable is proxied by Net Profit Margin (NPM), Return on Asset (ROA), Return on Equity (ROE), and Capital Adequacy Ratio (CAR). The sample in this study is Sharia Commercial Bank which registered in Bank Indonesia. The sample was selected using purposive sampling method and obtained six bank being sampled. This study used a non parametric statistical Spearman correlation test to analyze the data. The result showed associations between Corporate Social Responsibility and Corporate Financial Performance. This study showed that there is a possitive relationship between CSR and ROE in the next year and there is a negative relationship between CAR and CSR in the next year.